Futility has no utility in resuscitation medicine. Issue 5 (1st October 2000) - Ardagh, Michael
Abstract : "Futility" is a word which means the absence of benefit. It has been used to describe an absence of utility in resuscitation endeavours but it fails to do this. Futility does not consider the harms of resuscitation and we should consider the balance of benefit and harm that results from our resuscitation endeavours. If a resuscitation is futile then any harm that ensues will bring about an unfavourable benefit/harm balance. However, even if the endeavour is not futile, by any definition, the benefit/harm balance may still be unfavourable if the harms that ensue are great. It is unlikely that we will ever achieve a consensus definition of futility and certainly not one that is applicable to every patient undergoing resuscitation. In the meantime our use of the term "futile", in the mistaken belief that it tells us whether it is worth resuscitating or not, has no utility as it will never succeed in telling us this. Furthermore we risk causing offence by use of the term and we risk harming the patient's autonomy by using futility as an overriding force. Instead we should consider the utility of our endeavours, for which an assessment of the harms of resuscitation should be added to our considerations of its benefit. This balance of benefit and harm should then be evaluated as best it can be from the patient's perspective. The words futile and futility should be abandoned by resuscitationists.